The Effect of Music on Procedural Analgesia and Anxiety of Patients Undergoing Diagnostic Facet Block for Low Back Pain - Çifci, Coşkun; Yalçın, Çiğdem; Salman, Mehmet Alper; Çelebi, Nalan; Şahin, Altan (Acta Medica, 2023)
Aim: Chronic back pain is a common health problem which deteriorates quality of life which may be managed by medical therapy, interventions and surgery. Interventional therapies, including facet blocks and facet denervations are used regularly. Music therapy may be used before or during the painful interventional procedures with or without sedation. The study was designed to assess the effects of listening to music on procedural analgesia and anxiety during diagnostic facet block procedure. Method: Volunteering 52 patients that were involved in the study were randomly allocated into intervention and control groups of 26 patients each. The intervention group listened to music of their choice, if they demanded or classical music with headphones during the procedure. The control group did not listen to music. A combination of midazolam, morphine and fentanyl were used for sedation and analgesia in both groups. Results: The majority of the patients were women (77%) and the mean age was 55. We used Numeric Rating Scale (NRS) to assess pain, Spielberger State Trait Anxiety Inventory-6 (STAI-6) to assess anxiety and Ramsay Sedation Scale to determine the clinical level of sedation. No clinical or statistical significant differences in pain scores between control and intervention groups were found, when sedation effect was corrected (p=0.68). Ramsey Sedation Scores and NRS Scores were similar. Mean STAI-6 Score s were 9.5 ± 0.611 in the intervention group and 12.5 ± 0.726 in the control group (mean ± SE). The reduction in anxiety scores was significant both clinically and statistically, when sedation effect was corrected (p=0.006). Conclusion: Listening to music is an easy to use method that may be effective to reduce anxiety in patients with chronic low back pain during facet block procedure.